Timor-Leste Economic Report, May 2021 : Charting a New Path - World Bank Group (World Bank, Washington, DC, 2021)
COVID-19 is spreading quickly throughout the country, despite early successes in containing the virus. Meanwhile, flooding and landslides have caused considerable human loss and economic damage. These compounding health and humanitarian emergencies are undermining the economic recovery in 2021, but the recent approval of a revised budget can alleviate the negative impacts. Economic activity has been weakened by the recent COVID-19 outbreak and the impact of Cyclone Seroja. GDP is forecast to grow by 1.8 percent in 2021, which is lower than the 3.1 projected in October 2020. The economy is expected to recover in the medium-term, but structural constraints will remain an impediment to faster growth. Reforms to boost productivity and competitiveness are critical. COVID-19 and recent floods have highlighted and exacerbated underlying weaknesses in Timor-Leste’s health system. Disruptions to health and nutrition services arising from these crises may have a multiplier effect on access to care for routine and essential care, setting back the country’s progress on health outcomes and human capital development.